2018
DOI: 10.21273/hortsci12351-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prebloom Pruning on 13C and 15N Distribution during Early Spring in Sweet Cherry

Abstract: In sweet cherry, highly advanced dwarf combinations using ‘Gisela’ rootstocks promote higher productivity than do more vigorous combinations but require maintaining the leaf area to fruit area (LA:F) ratio. An experiment using double isotopic enrichment with 13C and 15N was carried out in 5-year-old ‘Bing’/‘GI 6’ trees in a commercial orchard located in Santa Cruz, Chile (34°39′S; 71°19′W), and characterized by a Mediterranean climate. Forty whole sweet cherry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
2
0
0
Order By: Relevance
“…Our study observed a reduction of shoot length on the trees pruned less severely, which was also documented in other studies (Usenik et al, 2008;Villasante et al, 2012), and may be explained by bet ter nitrogen use efficiency by extension shoots on pruned branches (Ayala et al, 2018). 'Krupnoplidna' trees also had decreased values of this indicator when pruned in late summer compared to dormancy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study observed a reduction of shoot length on the trees pruned less severely, which was also documented in other studies (Usenik et al, 2008;Villasante et al, 2012), and may be explained by bet ter nitrogen use efficiency by extension shoots on pruned branches (Ayala et al, 2018). 'Krupnoplidna' trees also had decreased values of this indicator when pruned in late summer compared to dormancy.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study are consistent with other trials on sweet cherry that report a yield increase when trees were unpruned or lightly pruned (Villasante et al, 2012;Claverie and Lauri, 2005). However, it should be noted that when trees enter full bearing, low pruning severity has a negative effect on fruit size and thus marketability of the yield (Gonkiewicz, 2011;von Bennewitz et al, 2011;Ayala et al, 2018), so more aggressive pruning may be need ed to manage crop load and maintain fruit quality.…”
Section: Discussionsupporting
confidence: 88%